If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(X + 5) + 4(X + -1) = 0 Reorder the terms: 2(5 + X) + 4(X + -1) = 0 (5 * 2 + X * 2) + 4(X + -1) = 0 (10 + 2X) + 4(X + -1) = 0 Reorder the terms: 10 + 2X + 4(-1 + X) = 0 10 + 2X + (-1 * 4 + X * 4) = 0 10 + 2X + (-4 + 4X) = 0 Reorder the terms: 10 + -4 + 2X + 4X = 0 Combine like terms: 10 + -4 = 6 6 + 2X + 4X = 0 Combine like terms: 2X + 4X = 6X 6 + 6X = 0 Solving 6 + 6X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6X = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 6X = 0 + -6 6X = 0 + -6 Combine like terms: 0 + -6 = -6 6X = -6 Divide each side by '6'. X = -1 Simplifying X = -1
| 20x+10y=70 | | 3x-9=-5x+23 | | 1.2d-1.6=6.8 | | 5(x+z)-7=5x+3 | | 13-3y=4 | | b^2+17b=0 | | 15-y=6 | | t/32=7/16 | | 7v+3=38 | | 150x=(120)(150)+120x | | 3w^2+6w+6=0 | | 8c=2c+24 | | 2-4(2+3a)=-2a+14 | | t=v+k | | 0.5x+2-1.5x=1.5x-6 | | 15x+2y=72 | | 4.3v-6=8+4b+3 | | 5+2*n=7-4*n | | 16t^2+32t+9=0 | | 15+4p=2 | | 145x=(115)(145)+115x | | 6x-7=x+8 | | 2r+44=5r+3r-20 | | y+2z=-9 | | 5+3*n=8-5*n | | 2a+3b=45 | | -7x-24+9x=18 | | 3x-5-5x=4-2x-9 | | 3x-(x+5)=5x-2(x+7) | | 6x-11=2x+15 | | 3x(x^2+8)=0 | | -2(3w+3)=12 |